Pharmacokinetics and Pharmacodynamics of Inorganic Nitrate in Heart Failure With Preserved Ejection Fraction. Issue 7 (31st March 2017) - Zamani, Payman; Tan, Victor; Soto-Calderon, Haideliza; Beraun, Melissa; Brandimarto, Jeffrey A.; Trieu, Lien; Varakantam, Swapna; Doulias, Paschalis-Thomas; Townsend, Raymond R.; Chittams, Jesse; Margulies, Kenneth B.; Cappola, Thomas P.; et al.
Abstract : Rationale: : Nitrate-rich beetroot juice has been shown to improve exercise capacity in heart failure with preserved ejection fraction, but studies using pharmacological preparations of inorganic nitrate are lacking. Objectives: : To determine (1) the dose–response effect of potassium nitrate (KNO3 ) on exercise capacity; (2) the population-specific pharmacokinetic and safety profile of KNO3 in heart failure with preserved ejection fraction. Methods and Results: : We randomized 12 subjects with heart failure with preserved ejection fraction to oral KNO3 (n=9) or potassium chloride (n=3). Subjects received 6 mmol twice daily during week 1, followed by 6 mmol thrice daily during week 2. Supine cycle ergometry was performed at baseline (visit 1) and after each week (visits 2 and 3). Quality of life was assessed with the Kansas City Cardiomyopathy Questionnaire. The primary efficacy outcome, peak O2 -uptake, did not significantly improve ( P =0.13). Exploratory outcomes included exercise duration and quality of life. Exercise duration increased significantly with KNO3 (visit 1: 9.87, 95% confidence interval [CI] 9.31–10.43 minutes; visit 2: 10.73, 95% CI 10.13–11.33 minute; visit 3: 11.61, 95% CI 11.05–12.17 minutes; P =0.002). Improvements in the Kansas City Cardiomyopathy Questionnaire total symptom (visit 1: 58.0, 95% CI 52.5–63.5; visit 2: 66.8, 95% CI 61.3–72.3; visit 3: 70.8, 95% CI 65.3–76.3; P =0.016) and functional status scores (visit 1: 62.2, 95% CI 58.5–66.0; visit 2: 68.6, 95% CI 64.9–72.3; visit 3: 71.1, 95% CI 67.3–74.8; P =0.01) were seen after KNO3 . Pronounced elevations in trough levels of nitric oxide metabolites occurred with KNO3 (visit 2: 199.5, 95% CI 98.7–300.2 μmol/L; visit 3: 471.8, 95% CI 377.8–565.8 μmol/L) versus baseline (visit 1: 38.0, 95% CI 0.00–132.0 μmol/L; P <0.001). KNO3 did not lead to clinically significant hypotension or methemoglobinemia. After 6 mmol of KNO3, systolic blood pressure was reduced by a maximum of 17.9 (95% CI −28.3 to −7.6) mm Hg 3.75 hours later. Peak nitric oxide metabolites concentrations were 259.3 (95% CI 176.2–342.4) μmol/L 3.5 hours after ingestion, and the median half-life was 73.0 (interquartile range 33.4–232.0) minutes. Conclusions: : KNO3 is potentially well tolerated and improves exercise duration and quality of life in heart failure with preserved ejection fraction. This study reinforces the efficacy of KNO3 and suggests that larger randomized trials are warranted. Clinical Trial Registration : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02256345 Abstract : Supplemental Digital Content is available in the text.